EXERCIZING IJTIHAD Fatwa and Ifta in Indonesia Today (JOURNAL OF INDONESIAN ISLAM, 2007)
Book ReviewBook title:Indonesian Islam: Social Change Through Contemporary FatawaAuthor:M.B. HookerNo. of Pages:X + 310Year:2003Publisher:Asian Studies Association of Australia, Allen and Unwin, and University of Hawaii Press Honolulu